The Application of Group Investigation (GI) Method to Improve the Students’ Interpersonal Intelligence in Social Sciences Learning - Umami, Fauzia (Universitas Pendidikan Indonesia, 2020)
This background of this research was the lack of the students’ interpersonal intelligence of Class VIII-A at SMP Negeri 14 Bandung during the learning of social sciences, marked by several students experiencing difficulties to socialize with their peers and tend to homogenicly choose their groupmates in order to form a group consisting of only their close friends. The Social Sciences’ course teachers then applied Group Investigation (GI) method to improve the students’ interpersonal intelligence during the teaching of Social Sciences. Interpersonal intelligence is gravely needed by students in Social Sciences learning, because individuals with excellent interpersonal intelligence level area able to communicate well and not having any trouble in establishing relationships with others. Based on the observation’s result, this research was conducted to further acknowledge how was the students of VIIIA’s interpersonal intelligence during Social Sciences learning process through application of Group Investigation method (GI). The research method used was descriptive qualitative with a data processing system which was suitable with the observation’s results during the application of Group Investigation (GI) method in Social Sciences in class VIII-A. The research results obtained showed that the application of Group Investigation (GI) method conducted by the teachers through topics selection by groups, planning, plan execution or action, analysis and evaluation, group presentations and evaluations in Social Sciences learning indicated changes in the students’ interpersonal intelligence in terms of communication and cooperation. That being said, a conclusion that the application of Group Investigation (GI) method in Social Sciences learning can inprove the students’ interpersonal intelligence.